2024
DOI: 10.1039/d3rp00245d
|View full text |Cite
|
Sign up to set email alerts
|

10 Guiding principles for learning in the laboratory

Michael K. Seery,
Hendra Y. Agustian,
Frederik V. Christiansen
et al.

Abstract: Laboratory work in chemistry has been extensively researched in the last decade but the gap between research and practice is still broad. This Perspective shares 10 guiding principles relating to university laboratory education, drawing on research over the last decade. Written with an audience of practitioners in mind, the Perspective aligns with Hounsell and Hounsell's congruence framework, so that the 10 principles consider all aspects of the laboratory curriculum: design, teaching approaches, and assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…We found that using this pre-lab exercise alone was not enough to significantly improve the students' performance, despite their perception of the assignment as being useful towards their learning. Consistent with others reports (Seery et al, 2024) we found that a potential predictor of student success is access to an instructor who directly assists them with learning proper technique.…”
Section: Discussionsupporting
confidence: 91%
“…We found that using this pre-lab exercise alone was not enough to significantly improve the students' performance, despite their perception of the assignment as being useful towards their learning. Consistent with others reports (Seery et al, 2024) we found that a potential predictor of student success is access to an instructor who directly assists them with learning proper technique.…”
Section: Discussionsupporting
confidence: 91%
“…54,56 This provides educators with the empirical evidence needed to make informed decisions rather than "gut instinct or personal experience" 61 about curriculum design called for in reforming general chemistry 62 and to "narrow the gap between research and practice" in the teaching lab. 63 ■ DESCRIPTION OF LABORATORY ACTIVITY This work was done within a general chemistry laboratory class at a large midwestern urban university serving a population with no majority ethnic or racial demographic. The laboratory is a two-credit, one-semester course taught independently of the introductory lecture course.…”
Section: Phenomenographymentioning
confidence: 99%
“…By analyzing undergraduate chemistry students’ written expressions through the lenses of meaningful learning and phenomenography, we present an outcome space that delineates students’ learning and their perceptions of spectrophotometry in the laboratory setting. These perceptions are grounded in students’ experience and are due to different patterns of awarenesshow individuals perceive and experience different components of the phenomenon. , This provides educators with the empirical evidence needed to make informed decisions rather than “gut instinct or personal experience” about curriculum design called for in reforming general chemistry and to “narrow the gap between research and practice” in the teaching lab …”
Section: Research Questionsmentioning
confidence: 99%
“…Reducing cognitive load on these students will incentivize them to concentrate on applying new concepts in the lab at a critical point in their development . This type of intervention falls under the actions to take in alignment with the Guiding Principle 8 proposed by Seery et al…”
Section: Introductionmentioning
confidence: 99%